Best dives [ Belize - Huber, Joyce; Huber, Jon (Hunter travel, 2009)
Based on the great classic, Best Dives of the Caribbean, this publication zeroes in on the best dives of Belize. Includes the latest and best dive and snorkel sites, each rated for visual excellence and marine life. The author's knowledge of the Caribbe